1997
DOI: 10.1046/j.1570-7458.1997.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of Orius laevigatus and Orius albidipennis on pollen and Ephestia kuehniella eggs

Abstract: Reproduction and longevity of the anthocorid predators Orius laevigatus (Fieber) and Orius albidipennis (Reuter) (Heteroptera: Anthocoridae) were studied under controlled conditions in the laboratory. Three different diets were tested: eggs of the Mediterranean flour moth, Ephestia kuehniella Zeller, E. kuehniella eggs plus pollen, and pollen only. Small rooted plants of Spanish pepper (Capsicum annuum L. cv. 'Creta', long red) served as oviposition substrate and moisture source. In all treatments, total fecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
3
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 10 publications
(30 reference statements)
3
82
3
10
Order By: Relevance
“…The Orius spp. in this area are likely to be well adapted to high temperatures, based on the results of a study on O. albidipennis (Cocuzza et al, 1997). The high cumulative survival (64.43%) recorded at 31°C indicates that O. similis is able to thrive at relatively high temperatures, although its survival at this temperature was lower than at 28°C (75.57%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Orius spp. in this area are likely to be well adapted to high temperatures, based on the results of a study on O. albidipennis (Cocuzza et al, 1997). The high cumulative survival (64.43%) recorded at 31°C indicates that O. similis is able to thrive at relatively high temperatures, although its survival at this temperature was lower than at 28°C (75.57%).…”
Section: Discussionmentioning
confidence: 99%
“…Adult females of O. similis need 5-6 days to complete the development of their reproductive system after (22) (Cocuzza et al, 1997) and on the spider mite T. urticae (approximately 100 eggs per female at most) at 25°C (Chyzik et al, 1995). It is unknown whether subtropical species of Orius are more likely to prey on thrips or T. urticae than T. cinnabarinus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also suggested that some nutrition contents in the diet might affect the fecundity of the bug. Many Orius species can be successfully reared on E. kuehniella eggs (Alauzet et al, 1992(Alauzet et al, , 1994Tommasini and Nicoli, 1993;Richards and Schmidt, 1996;Cocuzza et al, 1997;Vacante et al, 1997;Honda et al, 1998;Yano et al, 2002). However, the existence of non-ovipositing females is an important problem from the viewpoint of quality control in the mass-production of Orius species as a biological control agent.…”
Section: Discussionmentioning
confidence: 99%
“…Zoophytophagous predators feed on prey and/or on plants (Agrawal et al, 1999;Eubanks and Denno;Coll and Guershon, 2002;Azevedo et al, 2007;Guedes et al, 2007) with benefits for biological control of insect pests by improving the maintenance of the populations of these natural enemies during periods of prey shortage (Cocuzza et al, 1997). However, the morphological features of the reproductive organs and the fecundity of predatory Pentatomidae can be affected by factors such as unfavorable environmental conditions and quantity or quality of the food (Lemos et al, 2005a;2005b).…”
Section: Introductionmentioning
confidence: 99%